185k views
0 votes
What is the solution to 2(6x+10)-3x=10-(x-2)

User Wilfred
by
4.6k points

1 Answer

6 votes

Answer:

The value of x is -4/5.

Explanation:

First, you have to get rid of brackets, by expanding out :

2(6x+10) - 3x = 10 - (x-2)

2(6x) + 2(10) - 3x = 10 - x + 2

12x + 20 - 3x = 10 - x + 2

Next, is to bring all the x variable to one side :

12x + 20 - 3x = 10 - x + 2

12x - 3x + x = 10 + 2 - 20

10x = -8

Lastly, is to solve it by dividing 10 to both sides :

10x = -8

10x ÷ 10 = -8 ÷ 10

x = -4/5

User Efremidze
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.